THE INFLUENCE OF JOB STRESS, SOCIAL SUPPORT, AND WORK–LIFE BALANCE ON HEALTHCARE WORKERS’ PERFORMANCE - Eka Hesti Hastuti; Vip Paramarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Healthcare professionals face unique psychological and organizational challenges that significantly affect their performance and well-being. This study aims to analyze the influence of job stress, social support, and work–life balance on the performance of healthcare workers through a comprehensive literature-based approach. Using a systematic review of relevant journal articles published between 2015 and 2025, this study synthesizes theoretical and empirical findings from reputable academic databases such as Google Scholar, ScienceDirect, and SpringerLink. The results reveal that job stress has a detrimental effect on healthcare workers’ performance, leading to emotional exhaustion, reduced concentration, and decreased service quality. In contrast, social support serves as a crucial protective factor that mitigates the negative impact of stress by fostering teamwork, motivation, and resilience. Moreover, a balanced work–life relationship enhances job satisfaction, psychological well-being, and organizational commitment, which collectively improve performance outcomes. Integrating these findings through the Job Demands–Resources (JD-R) Model indicates that while job stress functions as a demand that depletes energy, social support and work–life balance serve as resources that replenish it. The study concludes that healthcare institutions must adopt holistic strategies to reduce occupational stress and strengthen support systems, promoting both employee well-being and sustainable performance.